Differences in Nutritional Value and Antioxidant Activity in Meat Products and Sausage Made of Bali Beef and Lamtoro Beef - Baiq Rani Dewi Wulandani; Bulkaini Bulkaini; Sukirno Sukirno; Djoko Kisworo; Wahid Yulianto; Haryanto Haryanto (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Processed meat products that are common and much preferred by the consumers are sausages and beef meatballs. This processed product has the disadvantage that it has a high-fat content, causing faster oxidative damage. This study aims to observe differences in the nutritional value and antioxidant activity of meatballs and sausages from Bali-beef and Lamtoro-beef. The main research material is fresh Bali-beef and lamtoro beef using several chemicals and laboratory equipment related to proximate analysis and antioxidant testing. The study was designed based on a Completely Randomized Design with 4 treatments and 3 replications and continued with Duncan's test SPSS version 16 programme. The results showed that the highest crude protein content was found in lamtoro-beef with lower fat content, water content, and ash content compared to fresh Bali-beef. Meatball and sausage products with the raw material of lamtoro-beef were not significantly (P>0.05) had a higher crude protein content than meatballs and sausages with the raw material of Balin-beef. The antioxidant activity of fresh Bali-beef and its processed products (meatballs and sausages) was not significantly (P>0.05) higher than the antioxidant activity of lamtoro-beef. Conclusion: Lamtoro-beef and its processed products in the form of meatballs and sausages have a higher protein content with lower fat content, water content and ash content compared to fresh Bali-beef. Meatball and sausage products made from fresh beef were not significantly (P>0.05) had higher antioxidant activity than lamtoro-beef.